DOI: 10.4203/csets.21.7
|View full text |Cite
|
Sign up to set email alerts
|

Ontologies, Agents and the Grid: An Overview

Abstract: Keywords: Software agents, Grid, resource brokering and management, ontology, semantic information processing.One of the important claims that permeate current view of information management is that ontological demarcation of data and semantic information processing are going to allow to infuse "intelligence" into information systems. Separately, it is claimed that software agents, combined with ontologies will be the foundation of Web 4.0. In our work we are developing an agent-team-based resource management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For example in the Grid Computing context, the main purpose of the Grid Laboratory for a Uniform Environment [11] (GLUE) schema was to allow interoperability between grid projects in the US and the EU by defining a schematic vocabulary with serializations to XML, LDAP and SQL [12]. The lack of formalism, and, as a consequence, the missing means to reason over the information, motivated the transition to a Semantic Open Grid Service Architecture [13] (S-OGSA).…”
Section: Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in the Grid Computing context, the main purpose of the Grid Laboratory for a Uniform Environment [11] (GLUE) schema was to allow interoperability between grid projects in the US and the EU by defining a schematic vocabulary with serializations to XML, LDAP and SQL [12]. The lack of formalism, and, as a consequence, the missing means to reason over the information, motivated the transition to a Semantic Open Grid Service Architecture [13] (S-OGSA).…”
Section: Computingmentioning
confidence: 99%
“…Fig. 7 shows the result of such a call using the client library jFed 12 . As highlighted, an RDF/JSON serialized description of the testbed has been embedded in the JSON based response data structure by adding a new node in the tree.…”
Section: B Software Integration Concepts Overviewmentioning
confidence: 99%
“…In the context of Grid Computing, the Grid Laboratory for a Uniform Environment (GLUE) [11] schema was started 15 years ago to support interoperability between Grid projects by defining a schematic vocabulary with serializations to XML, LDAP, and SQL [12]. A lack of formalism and a consequent inability to perform logical operations on data motivated the transition to Semantic Open Grid Service Architecture (S-OGSA) [13].…”
Section: Semantic Models For Grids Clouds and Iotmentioning
confidence: 99%
“…Preliminary research in this area involved analyzing existing Grid ontologies (see [18]). On the basis of this analysis it was concluded that the closest and the most adequate ontology, for the AiG system, was the Core Grid Ontology (CGO ; [19,20]).…”
mentioning
confidence: 99%